This book is gay eaudiobook - Dawson, Juno (Tantor Media, 2017)
Lesbian. Bisexual. Queer. Transgender. Straight. Curious. This book is for everyone, regardless of gender or sexual preference. This book is for anyone who's ever dared to wonder. This book is for you . There's a long-running joke that, after "coming out," a lesbian, gay guy, bisexual, or trans person should receive a membership card and instruction manual. This is that instruction manual. You're welcome. Inside you'll find the answers to all the questions you ever wanted to ask: from sex to politics and hooking up to stereotypes, coming out, and more. This candid, funny, and uncensored exploration of sexuality and what it's like to grow up LGBT also includes real stories from people across the gender and sexual spectrums. You will be entertained. You will be informed. But most importantly, you will know that however you identify (or don't) and whomever you love, you are exceptional. You matter. And so does this book.